Factors Affecting Longer Surgical Times in Total Knee Arthroplasty for Obese Patients—A Comparative Study between High- and Nonhigh-Volume Surgeons - Harato, Kengo; Kobayashi, Shu; Nagashima, Masaki; Hasegawa, Takayuki; Tanikawa, Hidenori; Maeno, Shinichi; Nomoto, So (The Journal of Knee Surgery, 2018)
Obesity has a negative influence on surgical times in total knee arthroplasty (TKA). Our purpose in this multicenter study was to compare surgical times between high- (HV) and nonhigh-volume (NHV) surgeons and clarify the important factors affecting longer surgical times in primary TKA for obese patients. A total of 798 knees, average age 75.1 years, were enrolled. All TKAs were done using the same measured resection technique by 25 surgeons at 12 facilities and were divided into three groups based on body mass index (kg/m2) of the patients (Group A: <24.9, Group B: 25–29.9, Group C: ≥30). Operative techniques including four surgical steps (surgical exposure, bone cutting, trial and fixation of the permanent component, and wound closure) were evaluated both in HV and NHV surgeons. In classifying surgeon volume, HV surgeons had performed >100 TKAs annually for many years, and other surgeons who had performed <100 TKAs annually were defined as NHV surgeons. Patient demographics, surgical details, and surgical times in each phase were compared using nonrepeated measures of analysis of variance and a post hoc Student–Newman–Keuls test. A total of 331, 327, 140 TKAs were allocated to Groups A, B, C, respectively. Regarding patient demographics, patients in Group C were younger and had the worst ranges of motion. The longest surgical time was observed in Group C of NHV surgeons (p < 0.05). Concerning each surgical phase, surgeons took much more time in surgical exposure and fixation of the permanent component for obese patients in NHV surgeons (p < 0.05). Our results suggest that younger age and lower range of motion were observed in obese patients, which led to longer surgical times. In addition, NHV surgeons took much time in surgical exposure and fixation of the permanent component for obese patients, while surgical time was similar among groups for HV surgeons.
Keywords: total knee arthroplasty; obesity; surgeon volume; surgical exposure; implant fixation